Alcohol consuming habits and its effects on adherence and blood glucose level in type-2 diabetes mellitus in a town population in eastern region of Nepal (Health Renaissance, 2011)
Introduction: Non-adherence to prescribed medications continues to be a major problem worldwide and mostly in developing countries like ours. Keeping blood glucose level normal has become the greatest challenge among alcohol consumers to the health personnel because of the different factors for non adherence to the drugs prescribed for diabetes. Objectives: To measure the magnitude of non- adherence to the prescribed medications along with the habit of alcohol consumption and the reasons of continuation of alcohol consumption along with the medication. Methods: A descriptive cross sectional study was carried out from February 2008 to July 2009 at diabetic clinic of Department of Medicine at BPKIHS, Dharan, Nepal. A total of 300 Type2 diabetic patients aged 24 years and above residing in Dharan Municipality in the eastern region of Nepal, taking treatment for diabetes for at least six months were included using convenient sampling method along with the informed consent and interviewed by reaching them individually to their houses. Results: The prevalence of nonadherence was 48%. Among the factors that were independently associated with non-adherence alcohol was also the main factor which played the significant role in non- adherence. Around 59% who had blood glucose level >126mg/dl were found non- adherent to the medicine because of several reasons and among them one was the habit of alcohol consuming at least once daily regardless the quality, quantity, brand and type of alcohol. Conclusions: Adherence to diabetic treatment was suboptimal. Alcohol has played a significant role in non- adherence. Blood glucose level among drinkers was found significantly higher than others. There is a need to improve the alcohol habits of the patients to improve the adherence to the drugs prescribed for the disease. Keywords: adherence; type 2 diabetes mellitus; alcohol; blood glucose level; Dharan Municipality DOI: http://dx.doi.org/10.3126/hren.v9i2.4981 Health Renaissance 2011: Vol.9 (No.2): 95-101